Audit of Disaster Communication on TVOne Kabar Petang Program - Puji Lestari; Devi Wening Astari; Aqmarina Laili Asyrafi (Ikatan Sarjana Komunikasi Indonesia, 2019)
This study aims to carry out a disaster communication audit of Kabar Petang (Evening News) Program on the TVOne in the May-June 2019 period. This study uses the SMCR theory and the concept of disaster communication, the Standard Operating Procedure (SOP) of Disaster Communication, and the Guide to Broadcasting Behavior and Standards of Broadcasting Programs issued by the Indonesian Broadcasting Commission (KPI). This study uses a descriptive qualitative method with data collection techniques including content analysis, observation, a document study, and validity test through an interview with KPI as a source. The results of this study constitute the findings of disaster communication audit of disaster broadcast on TVOne, part of which has followed the Guide to Broadcasting Behavior and the Standards of Broadcasting Program issued by the KPI, SMCR theory, and has used disaster communication dimensions, and SOP for Disaster Communication. There are some findings that are not yet suitable, namely: (1) the repetition of a video clip showing the sufferings of victims; (2) the absence of competent resource persons in the field of disaster; and (3) the broadcast of affected people’s panic. This research provides recommendations to broadcasting institution TVOne, the government, and media workers to convey educational broadcast messages based on competent sources in the field of disaster so that the community is ready to survive the natural disaster.